An organizational theory of unionization - Anja Prummer; Francesco Squintani (Freie Universität Berlin, School of Business & Economics, 2024)
Motivated by the recent surge in union drives, we present a theoretical model of the factors that influence unionization. An employee seeking to unionize their workplace assembles organizers to persuade coworkers to vote in favor. If unionization benefits workers, it is more likely to succeed when the organizers are credible. Credibility depends on the organizers not being overly biased and/or bearing significant organizational costs. Our theory explains why grassroots movements, rather than established unions, often succeed in organizing workplaces. Interestingly, the likelihood of successful unionization, when it benefits workers, is non-monotonic with respect to organizational costs. When such costs are low, a firm that opposes unionization and targets organizers may paradoxically increase the chances of success. However, the unionization drive is ineffective if the firm's opposition is sufficiently strong, as this makes organizational costs prohibitive.
urn:nbn:de:kobv:188-refubium-45833-1
Keywords: D71; D83; D23; 330; Unions; Labor Organization; Campaigns